Constructivist stream in Ukrainian soviet fashion of 1920 - Glushko, Yu. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
CONSTRUCTIVIST STREAM IN UKRAINIAN SOVIET FASHION OF 1920 Abstract. Introduction. The article traces the impact of the art constructivism on the fashion’s advancement in the Soviet state in 1920ies. Purpose. This research aims to analyze the role of the avant-garde art in the branch of the fashion clothes’ industrial projecting. Results. In totalitarian societies, fashion is the instrument of the new social consciousness’s, mass-views’ and tastes’ formation. During the first decades of USSR’s existing, the constructivist artists were involved in these tasks’ realization because they assert the art’s transforming role. The goal of constructivism was changing of the Soviet society’s everyday surrounding by the implementation of utilitarian working clothes for different branches of industry. During the realization of the new vision of industrial art, the first attempt of constructivists was creating of the specific textile concept. Using the constructivist textile, they wanted to solve the problem of industrial producing of clothes for defeating the deficiency of goods. But the modern textile samples had been very soon ousted by traditional ornaments. The artists also created the samples of clothes which, on the one hand, embodied the art and style principles of constructivism – bright and contrast colors, regular geometric forms, and removable parts. On the other hand, these samples were in accordance with the state demands – full absence of décor, asceticism, economical. Originality. This research article doesn’t pretend on the exhaustive disclosure of Ukrainian Soviet fashion’s advancement. It clarifies the details of the interaction between fashion, state demands, and constructivism. Conclusion. The achievements of constructivists in new types’ of Soviet clothes creation weren’t fully implemented in the everyday life sphere. In general, these achievements stayed in the sketch form. The submission of the art to the state and traditional esthetic’s returning reduced the impact of constructivism on the textile and clothes industry. But this art experiment was the first attempt of the own unique conception’s creation for the young Soviet state.